The Personal Characteristics that Influence Tax Auditors' Conciliatory Style: An Empirical Study - Nordin, ZS; Muhammad, I; Abd Wahab, K; Yaakub, NA (Univ Putra Malaysia Press, 2024)
The way a tax auditor deals with taxpayers can give an impact on audit settlement outcomes. Qualitative studies show that tax auditors often use the conciliatory style as a strategy to resolve disputes because it expedites audit settlement and promotes long-term compliance. However, there is no study that has empirically examined the factors that influence tax auditors' conciliatory style. This study aims to examine the influence of personal characteristics i.e. attitude towards achieving goals, experience and ethical ideology on tax auditors' conciliatory style in resolving audit settlement disputes. Six hundred and thirty-six questionnaires (63.6% of response rate) were usable for data analysis. The results revealed that all the personal characteristics surveyed significantly influenced tax auditors' conciliatory style. This study can extend the literature on tax auditors' behaviour and facilitate the Inland Revenue Board of Malaysia in better understanding their auditors.